EFFECT OF IONIC STRENGTH FROM DIFFERENT SALT RESOURCES ON BORON ADSORPTION IN CALCAREOUS SOIL - Nasser, K. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was conducted in the laboratories of Soil and water resources Department, College of Agricultural Sciences Engineering, University of Baghdad for the purpose of disclosing the effect of ionic strength from different salt mixtures on the adsorption of Boron in a silty clay loam calcareous soil taken from the prior location of the college of Agriculture in Abu Ghraib, after a quite equilibrium of Boron solution prepared from Boric acid at( 0, 1, 5, 7.5, 10 and 20) μmole B.ml-1 at 298 Kalvin. Three solutions with different ionic strength were used( 0.1, 0.2, 0.3) mole.L-1 of four different salts CaCl2, MgCl2, NaCl and composed salt of the three salts at 3:1:1 ratios respectively. Langmuir single surface line equation was used for better description of the reactions of Boron adsorption in soil.Results showed a significant increase in Boron adsorbed quantity in soil with the increase of the applied Boron. The increase in ionic strength led to a significant increase in adsorbed Boron for all salts with different rates. These different salts showed significant differences in adsorbed quantity of Boron, where CaCl2 treatment was exceeded followed by MgCl2, mixture salt, then NaCl treatments as an averages of the three ionic strengths where it reached (68.95, 65.26, 58.38 and 44.37) μmole B.gm-1 soil respectively and at maximum adsorption capacity (Xm) at (58.26, 55.92, 47.90, 46.17) mg B. Kg-1 soil, while bonding energy to soil particles (K) was  (0.279, 0.244, 0.244 and 0.125) ml μ B for the mentioned salts respectively. In general, soil is considered to have a high maximum adsorption capacity (42.88 mg B.Kg-1 soil) and low bonding energy (0.216 ml μ-1 B) .